Racism and Its Effect on Social Cohesion in South Africa: A Student Perspective - Bongani Innocent Dlamini; Emmanuel Lawa; Hlanganani Siduduzo Shange; Luther-King Junior Zogli (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
Racism has become an integral part of everyday life in South Africa, and some analysts say that it is time to address this issue. The race war continues to rage in South Africa, especially on social media. South Africa has emerged from a very painful past, a past that some South Africans find very difficult to talk about and forget. South Africans mainly view themselves along colour lines. Conversations about race have always been an issue; black people, have particularly been discriminated against based on their skin colour. The world, in general, seems to be battling with the scourge and the scars of racism and South Africa is no exception. It can be argued that racism itself is a very old phenomenon and therefore laws have been enacted to bring about order to protect citizens. In recent years, South Africa has been characterized by statements that seek to divide the nation along colour lines. This study aimed to assess the perceptions of students towards racism and provide recommendations on how to minimize its effects and promote nation-building and a common understanding. The study followed a qualitative approach, where data was collected using in-depth interviews and analysed thematically.